Perbedaan Angka Kejadian Sindrom Syok Dengue (SSD) Antara Anak Dengan Gizi Baik Dan Gizi Lebih - Sapitri, Risya Nur Fadillah, Prof.DR.Dr.Bambang Subagyo, Sp.A. (K.) (2017)
The incidence of dengue continues to grow from year to year with a mortality rate that remains high and will increase when developed into Dengue Shock Syndrome (SSD). Some research suggests the opposite result of child nutrition (overweight and obese) with dengue infection are more at risk for experiencing SSD compared to well-nourished children. The aim of research to determine differences in the incidence of Dengue Shock Syndrome (SSD) among children good nutrition and over nutrition in hospitals Dr. Moewardi. This study was an observational analytic with cross sectional approach. during the period research, found 31 cases of dengue fever and 31 cases of dengue shock syndrome, according to WHO criteria and tested by chi-square test, the result p = 0.01 (<0.05), which means statistically significant. The incidence of children with better nutrition, greater than well-nourished children and there is a significant difference between the proportion of children with good nutrition and nutrition in the incidence of Dengue Shock Syndrome (SSD) in the Hospital Dr. Moewardi Surakarta.